Analysis of cake compressibility of high fouling feedwater from a hybrid PAC-MF process - Amosa, Mutiu Kolade; Jami, Mohammed Saedi (2015)
This study investigates the utility of a hybrid adsorption-membrane process for cake compressibility evaluation of biotreated palm oil mill effluent (BPOME). A low-cost empty fruit bunch (EFB) based powdered activated carbon (PAC) was employed for the upstream adsorption process with operation conditions of 60 g/L PAC dose, 68 min mixing time, and 200 rpm mixing speed to reduce the feed-water strength and alleviate probable fouling of the membranes. Two polyethersulfone microfiltration (MF) membranes of 0.1 and 0.2 µm pore sizes were investigated under constant transmembrane pressures (TMP) of 40, 80, and 120 kPa. The compressibility factors (z), which was obtained from the slopes of power plots (function of specific cake resistance (α) and pressure gradient) were evaluated. The z values of 0.32 and 0.52, respectively obtained, for the 0.1 and 0.2 µm MF membranes provided compressible and stable z values as observed from their power plots. Besides, these membranes were found suitable for the measurement of z since the results are in consonance with the established principle of cake compressibility. Moreover, the upstream adsorption mitigated the clogging of the membranes which ultimately led to moderate resistances and cake compressibility. These are indications that with the secondary cake filtration, a sustainable flux can be achieved during BPOME filtration. The membranes exhibited close to 100% restoration after cleaning.